Development of a database on tumors and tumor sites in humans and in experimental animals for 'Group 1 agents identified through volume 109 of the IARC Monographs. (17th November 2019) - Grosse, Yann; Lajoie, Pascale; Billard, Mélissa; Krewski, Daniel; Rice, Jerry; Baan, Robert A.; Cogliano, Vincent; Bird, Michael; Zielinski, Jan M.
ABSTRACT: Volume 100 in the series of IARC Monographs on the Evaluation of Carcinogenic Risks to Humans comprises an update and review of relevant information on all agents determined to induce cancer in humans. These Group 1 agents are categorized in 6 Monographs (Volumes 100A-F) published in 2012. This paper describes the methodology and stringent criteria used in the creation of a comprehensive database on tumors noted in animals and humans for the carcinogens reviewed in Volume 100, and for additional Group 1 agents that were identified in subsequent Monographs through Volume 109. The development of this database involved the systematic collection of relevant data on tumors detected in humans and experimental animals identified by the Working Groups that conducted evaluations reported in the IARC Monographs . The database includes all human tumor sites identified by the Working Groups, along with all tumor sites for which there was sufficient evidence in experimental animals. This database provides a basis for assessing the degree of concordance between tumor sites observed in humans and experimental animals for Group 1 agents identified through Volume 109.